Diseño e implementación de una aplicación web que permita calcular el índice de fragilidad (2019)
According to the World Health Organization (WHO), today there are around 600 million people over the age of 60 in the world. By 2050, the proportion of the planet's inhabitants in this age range will double, from 11% to 22%. Globally, the aging of the population is of special importance to nations for its economic, medical and social implications. Based on the above, it is evident that the aging of the population has profound implications for the planning and delivery of health and social care. It is there when a new concept of vital importance emerges, which is the condition of fragility. Frailty can be defined as a clinical state where there is an increase in the vulnerability of a person to develop greater dependency and / or mortality when exposed to stressors. In this way, the present research work aims to design and implement a web application, in order to calculate the fragility index in people of both sexes over 25 years of age, through the use of the CaMos fragility scale.